Psycho-Social Adjustment of Adolescents of Working and Non –Working Mothers: An Exploratory Study - Sandhu, Dr. Dayal (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to compare the psycho – social adjustment of adolescent children of working and non- working mothers of Bulandshahr district. The sample consisted of 100 children of working and non - working mothers with age range of 13 to 18 years. In this study the adjustment inventory for school students by A.K.P Sinha and R.P Singh (1988) has been used a tool for Data Collection obtained data was analyzed by mean, S.D, t. test. Results revealed that there was no significant difference between the psychos – social adjustment of adolescent children of working and non – working mothers.